2022
DOI: 10.1126/sciadv.abn8485
|View full text |Cite
|
Sign up to set email alerts
|

The developmental origin and the specification of the adrenal cortex in humans and cynomolgus monkeys

Abstract: Development of the adrenal cortex, a vital endocrine organ, originates in the adrenogonadal primordium, a common progenitor for both the adrenocortical and gonadal lineages in rodents. In contrast, we find that in humans and cynomolgus monkeys, the adrenocortical lineage originates in a temporally and spatially distinct fashion from the gonadal lineage, arising earlier and more anteriorly within the coelomic epithelium. The adrenal primordium arises from adrenogenic coelomic epithelium via an epithelial-to-mes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(82 citation statements)
references
References 34 publications
6
74
0
Order By: Relevance
“…Unexpectedly, we also identified minor off-target cell types including CLDN5 + KDR + endothelial-like cells and ASCL1 + GATA3 + PHOX2B + TH + DBH + sympathoadrenal-like cells of uncertain origin (Extended Data Fig. 6b, e) 12 . Notably, trajectory analyses also revealed two additional lineages that appear to project from PIM/CE-like cells, thus sharing their origin with adrenocortical lineages.…”
Section: Scrna-seq Revealed Lineage Trajectories Of On-target and Off...mentioning
confidence: 84%
See 2 more Smart Citations
“…Unexpectedly, we also identified minor off-target cell types including CLDN5 + KDR + endothelial-like cells and ASCL1 + GATA3 + PHOX2B + TH + DBH + sympathoadrenal-like cells of uncertain origin (Extended Data Fig. 6b, e) 12 . Notably, trajectory analyses also revealed two additional lineages that appear to project from PIM/CE-like cells, thus sharing their origin with adrenocortical lineages.…”
Section: Scrna-seq Revealed Lineage Trajectories Of On-target and Off...mentioning
confidence: 84%
“…We have previously demonstrated that human fetal adrenal cortex strongly expresses DLK1, a membrane bound protein that negatively regulates NOTCH signaling 12,15 . Moreover, Sonic Hedgehog (SHH) is thought to be critical for adrenocortical development, and downstream genes of SHH are highly expressed in human fetal adrenal cortex 12,[19][20][21] . This motivated us to test the effect of DAPT (NOTCH inhibitor) and SHH on NT expression.…”
Section: Induction Of Early Adrenocortical Lineage Through Posterior ...mentioning
confidence: 99%
See 1 more Smart Citation
“…E1 and E2 is then transported from the placenta into the maternal the 'transitional zone' (TZ), develops between the DZ and FZ after mid-gestation [38,39]. Pseudotemporal ordering of cell transcriptomes from human embryonic adrenal cells suggests that the DZ originates directly from cells of the AP, whereas the FZ can both derive from the AP or from DZ cells [8]. Finally, the FZ is destined to disappear by apoptosis soon after birth, resulting in an about 20-time decrease in adrenal mass from the 4-5 g full-term adrenal, and a rapid fall in the production of androgen precursors, namely dehydroepiandrosterone (DHEA) and dehydroepiandrosteronesulfate (DHEA-S) [40,41].…”
Section: Fetal Adrenal Function and Its Role In The Fetal-placental S...mentioning
confidence: 99%
“…These in vitro data are fully consistent with the higher SF-1 expression in FZ cells compared to DZ cells (Figure 2H). [72] Another factor limiting SF-1 activity prevalently in the DZ is the transcriptional repressor DAX-1/NR0B1. [73] (A) SF-1 was shown to activate expression of the rat PRLR gene in a steroidogenic cell line.…”
Section: Hypothesismentioning
confidence: 99%